Legal Protection for Victims in The Resolution of Criminal Cases Through Restorative Justice Mechanisms - Widya Ari Dewi; Satya Arinanto; Muhammad Ilham Hermawan (Jurnal Daulat Hukum, 2025)
The application of restorative justice within Indonesia’s criminal justice system has developed significantly alongside the enactment of various regulations governing restorative-based case resolution. However, in practice, this mechanism continues to face fundamental challenges concerning the legal protection of victims. This study aims to analyze the legal protection afforded to victims in criminal case resolution through restorative justice, identify normative gaps and regulatory disharmony, and formulate an ideal model of victim protection oriented toward victim-centered justice. The research employs a normative juridical method with statutory and conceptual approaches through library research. The findings indicate that although a normative framework for restorative justice exists, victim protection has not been comprehensively integrated. Differences in standards of victim voluntariness, the absence of proportional compensation guidelines, and weak post-agreement monitoring mechanisms potentially place victims in vulnerable positions and open space for revictimization. From a human rights perspective, these conditions demonstrate that restorative justice has not yet been fully implemented as an instrument for fulfilling victims’ rights. This study proposes an ideal model of victim protection in restorative justice that emphasizes layered protection at the pre-process, process, and post-agreement stages as an effort to strengthen substantive justice.